2015
DOI: 10.15517/rbt.v63i3.16242
|View full text |Cite
|
Sign up to set email alerts
|

Crecimiento y producción de Donax striatus (Bivalvia: Donacidae) en playa Las Balsas, Gibara, Cuba

Abstract: Clams of the genus Donax are worldwide the dominating group of the invertebrate community on sandy beaches. They are primary consumers that provide a significant abundance and biomass to the ecosystem. In the Caribbean, Donax striatus has an important role for nature and human, nonetheless studies on the population dynamics of this beach clam are scarce and no information exists on secondary production of this species. Growth parameters and secondary production of D. striatus were estimated from February 2008 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 15 publications
0
7
1
4
Order By: Relevance
“…Contrary to reports for other Donax populations in the Caribbean (Sastre, 1984;McLachlan et al 1996;Ocaña et al 2010) showing temporal differences in abundance, D. denticulatus at Levisa Beach had no significant changes in abundance throughout the study period. The same pattern was observed by Ocaña et al (2013) with this species at Carenero Beach.…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…Contrary to reports for other Donax populations in the Caribbean (Sastre, 1984;McLachlan et al 1996;Ocaña et al 2010) showing temporal differences in abundance, D. denticulatus at Levisa Beach had no significant changes in abundance throughout the study period. The same pattern was observed by Ocaña et al (2013) with this species at Carenero Beach.…”
Section: Discussioncontrasting
confidence: 94%
“…One of the accepted explanations is that zonation by size represents a mechanism to avoid intraspecific competition (McLachlan et al 1996). It is suggested that the middle intertidal zone is a more favorable habitat for intertidal species because individuals are not constantly exposed to the continuous wave action, the zone is always saturated and the sediment is medium sized compared to the lower and upper zones; consequently, organisms do not have to divert a lot of energy to maintain their position and to avoid being washed by waves (Ocaña et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Samples with larger lengths are slower in reaching their maximum length compared to others with smaller lengths (Sparre and Venema 1999). However, the clams in Kendari Bay had relatively faster growth than others, including Donax striatus (Ocaña 2015), Lithophaga patagonica (Bagur et al 2013), Dosinia ponderosa, Megapitaria aurantiaca, and Megapitaria squalida (Lopez- Rocha et al 2018). They also had similar rates to Geloina expansa (Yahya et al 2018), Darina solenoides (Lizarralde et al 2018) as well as slower rates to Eumarcia paupercula (Mugabe et al 2019), Crassostrea lass (Yapia et al 2017, and Anomalocardia brasiliana (Mattos and Cardoso 2012).…”
Section: Growthmentioning
confidence: 96%
“…a dan b = konstanta L = lebar cangkang (mm) MKBA = massa kering bebas cangkang (gram) Kepadatan kerang pokea (B. violacea) setiap bulan dianalis dengan persamaan (Ocaña et al, 2015): = / ……….…………………………………………………………………………………………………(2) Keterangan: K = kepadatan (ind./m 2 ), Ni = jumlah individu (ind.) A = luas area (m 2 ) Total produksi tahunan (annual production) (P (gMKBC/m 2 .yr)), diduga dengan nilai MKBC dari semua sampel menggunakan metode laju pertumbuhan massa spesifik (masss pecific growth rate method) (Crisp, 1984) dari data kepadatan, frekuensi kelas-ukuran, parameter pertumbuhan vBGF dan hubungan panjang-bobot, sebagai berikut (Laudien et al, 2003):…”
Section: Analisis Statistikunclassified